Wyoming wild [large type] - Eden, Sarah M. (Proper romance., 2023)
"US Marshal John "Hawk" Hawking is one of the most respected lawmen in the West--a fair but firm man of principle and decisive action--so when a telegram arrives from the small town of Sand Creek warning him of a death threat against him, he immediately begins an investigation. Posing as a farmer, Hawk heads to Sand Creek, a town ruled by a violent and corrupt sheriff who uses his position to menace, exploit, and tax the townspeople to the point of starvation. Only one person is trying to stop him--Liesl, the sheriff's own daughter. When she meets the self-assured and attractive new farmer, John, she hopes he might help her in her long and lonely fight for justice. John is completely unfazed by Sheriff Hodges's attempts at intimidation, and Liesl is quickly swept up by Hawk's courage and integrity. Just as quickly, Hawk finds himself falling for Liesl's strength and bravery, as well as her grace and beauty. When Liesl discovers that John is not who he claims to be, she feels betrayed. Despite her lingering distrust of Hawk, Liesl agrees to work with him to enact a dangerous plan that will put the criminals away forever. Liesl must put her life, and her heart, in the hands of this lawman if she has any hope of saving her family and her town"--